Mowa pacjentki z chorobą Parkinsona w fazie zaawansowanej - Szurek, Mateusz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The purpose of this article is to present speech disorders of 91 years old patient suffering from advanced Parkinson’s disease (it is the last stage of the disease when all symptoms are stronger) and to draw attention to the need of mentioning the impact of speech therapy while describing the disease. In the article an author is introducing the patient and her current condition. Mainly it is focused on the speech therapy diagnosis that was based on particular aspects of speech (such as: general condition of the patient, phonation, comprehension of speech and naming, repea- ting, dialogues and storytelling, reading, counting and writing). In the final part, the effectiveness of speech therapy is presented. This publication might become a leading example for other speech therapist on how to manage the therapy for people suffering from these types of disorders in speaking and communication.